Hepatoprotective effect of Stachys pilifera ethanol extract in carbon tetrachloride-induce hepatotoxicity in rats - Esmaeel Panahi Kokhdan; Kyomarth Ahmadi; Heibatollah Sadeghi; Hossein Sadeghi; Fahemeh Dadgary; Nazanin Danaei; Mahmoud Reza Aghamaali (Taylor & Francis Group, 2017)
Context: Stachys pilifera Benth (Lamiaceae) has long been used to treat infectious diseases, respiratory and rheumatoid disorders in Iranian folk medicine. Antitumor and antioxidant activity of the plant have been reported. Objective: The study was designed to assess the hepatoprotective activity of ethanol extract of Stachys pilifera in carbon tetrachloride (CCl4)-induced hepatotoxicity in rats. Materials and methods: The rats were randomly divided into six equal groups (n = 7). Group I was treated with normal saline; Group II received CCl4 (1 mL/kg. i.p., twice a week) for 60 consecutive days; Groups III, IV and V were given CCl4 plus Stachys pilifera (100, 200 and 400 mg/kg/d,p.o.); Group VI received the extract (400 mg/kg/d, p.o.). Histopathological analysis and measurement of serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), malondialdehyde (MDA), total protein (TP) and albumin (ALB) were performed. Results: CCl4 caused a significant increase in the serum levels of AST, ALT, ALP and MDA as well as decreased ALB, and TP serum levels (p < 0.001). The extract (200 and 400 mg/kg/d) significantly normalized the CCl4-elevated levels of ALT, AST, ALP and MDA (p < 0.001). The extract (200 and 400 mg/kg/d) also increased the serum levels of TP compared to CCl4 group (p< 0.01). The extract (200 and 400 mg/kg/d) also decreased the histological injuries (inflammation and fatty degeneration) by CCl4. Discussion: The results revealed that the Stachys pilifera extract could provide considerable protection against CCl4 hepatotoxicity in rats that may be related to its antioxidant properties.